Oxidization of 4-nitrotoluene by nitric acid under excessive pressure and high temperatures - Бушуєв, Андрій Сергійович (Eastern-European Journal of Enterprise Technologies, 2013)
The article studies the kinetics of oxidation of 4-nitrotoluene by nitric acid under excessive pressure and high temperatures. The article investigates the influence of temperature and duration of oxidation on the qualitative and quantitative characteristics of the product - corresponding 4-nitrobenzoic acid. The determination of content of 4-nitrobenzoic acid was carried out by the titration method and electrometric titration. It was found that with proper choice of parameters, namely, the pressure in the reactor 60 atm, temperature 180 º C, duration 15 minutes and modules HNO3 = 2, the oxidation by 30% nitric acid can be carried out with high efficiency with maximum output of 4 -nitrobenzoic acid 95%. Thus obtained desired product is characterized by high quality (98,5-99,0% of 4-nitrobenzoic acid). It was found that the increase of the concentration of nitric acid over 45-50% leads to nitration of 4-nitrotoluenu to aromatic ring. Taking into account the use of the regenerated nitric acid it was recommended to limit the upper concentration to 50%. Thus, the results of these studies can be used to optimize obtaining of 4-nitrobenzoic acid at factories for its synthesis